Virtual reality and augmented reality in mobile shopping: an empirical study - Yao, Dianchen (2018)
Online shopping has become one of the major channels for people to do their daily shopping. Conducting online shopping with mobile phones, also known as mobile shopping, has become popular in the past years, due to the rapid growth of smart mobile phones and high-speed cellular networks. However, statistics show that the conversion rate of mobile shopping is significantly lower comparing to that of physical stores. Researches find that the main driver of the lower conversion rate is the poor shopping experience including bad navigation and product discovery experience, missing critical product information, unable validate the texture or test the fit of the product when conducting mobile shopping. Researches on Virtual Reality (VR) and Augmented Reality (AR) technologies indicate that these technologies can mimic the physical store shopping experience and solve some of the problems which drive low conversion rate in mobile shopping. Hence, this study aims to examine whether the AR and VR technologies can be used to improve the mobile shopping experience. Additionally, if these technologies can improve the mobile shopping experience, this study attempts to find out which are the factors contribute to the improved experience. Lastly, the study set to evaluation whether the mobile shopping experience created with VR and AR technologies can be well accepted and adopted by the public. As this study involves getting participants to shop with VR and AR gears in specific setups, experiment method is adopted to control the environment to avoid disturbance. Experiment 1 was designed to compare the experience of mobile shopping with and without VR technologies involved, and Experiment 2 was designed to compare the experience with and without AR technologies involved. Twenty people were recruited to participate in both experiments. Post experiments, they were asked to answer a short survey followed by an in-depth interview to share their opinions on their shopping experience. Results showed that both VR and AR technologies could play a role in improving the mobile shopping experience. Additionally, the improvements in user experience are contributed by the better shopping effectiveness and satisfaction created when using VR and AR technologies in mobile shopping. Moreover, it was found that mobile shopping experience created with VR and AR technologies are likely to be well-received and adopted by the public, since they have good perceived ease of use, perceived usefulness and perceived enjoyment. The study was concluded with theoretical and practical implications of the findings.